‘New urbanism’ or metropolitan-level centralization? A comparison of the influences of metropolitan-level and neighborhood-level urban form characteristics on travel behavior. - Petter Naess (Journal of Transport and Land Use, 2011)
Based on a study in Copenhagen Metropolitan Area, this paper compares the influences of macro-level and micro-level urban form characteristics on the respondents’ traveling distance by car on weekdays. The Copenhagen study shows that metropolitan-scale urban structural variables generally exert stronger influences than neighborhood-scale built environment characteristics on the amount of car travel. In particular, the location of the residence relative to the main city center of the metropolitan region shows a strong effect. Some local scale variables often mentioned in the literature as influential, such as the street pattern in the neighborhood, show no significant effect on car travel when control is made for the location of the dwelling relative to the city center.